Letter: is female sex really associated with better prognosis in hepatocellular carcinoma?. Issue 5 (10th February 2021) - Pelizzaro, Filippo; Penzo, Barbara; Trevisani, Franco; Farinati, Fabio; ,
Abstract : LINKED CONTENT This article is linked to Rich et al paper. To view this article, visit https://doi.org/10.1111/apt.15917